3.5k views
1 vote
Solve the equation 3(m + 5) = 3 + 3(2m + 2) for m.

User Sakthivel
by
7.4k points

2 Answers

0 votes

Answer:


m=2

Explanation:


3\left(m+5\right)=3+3\left(2m+2\right)

Expand:


3m+3*5=3+3*2m+3*2


3m+15=3+6m+6


3m+15=6m+9

Subtract 15 from both sides:


3m+15-15=6m+9-15


3m=6m-6

Subtract 6m from both sides:


3m-6m=6m-6-6m


-3m=-6

Divide both sides by -3:


(-3m)/(-3)=(-6)/(-3)


m=2

User Ogulcan Orhan
by
7.0k points
2 votes

Answer:

m=2

Explanation:

User Bird
by
7.5k points